Pengaruh Konten TikTok terhadap Perubahan Perilaku Menjaga Kebersihan Pengikut Pandawara Group - Bernadeth, Gabriella Yosiana; Junaidi, Ahmad (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The phenomenon of unbalanced waste accumulation in its management requires collective awareness and community involvement in overcoming and preventing the intensity of waste accumulation. Entering the digital era opens many opportunities for Pandawara Group in spreading effective social movements, social movements are carried out by Pandawara Group through the TikTok platform with the aim of reducing waste and expect awareness of maintaining the cleanliness of the Indonesian people to be embedded as an effort to deal with the phenomenon of waste accumulation. Therefore, researchers chose the topic of the influence of Pandawara Group's TikTok content on its followers in maintaining cleanliness. This research uses new media theory, persuasive communication, and planned behavior theory as research identification. This research uses a quantitative approach with descriptive research methods. Sampling technique using Probability Sampling - Simple Random Sampling with Cochran formula through questionnaire method data collection. The total number of respondents in the study amounted to 96 people. The population and sample of the study were TikTok Pandawara Group followers aged teenager-adult (15-35 years). The study found a Spearman Rank correlation value that there was a significant influence of 0.001, there was a very strong and unidirectional relationship strength with a value of 0.783 on TikTok content with behavior change. This study included the results of Crosstabs Spearman Correlation with the aim of deepening the meaning of research through age categories and TikTok content with a significance value of 0.891, age categories and behavior changes with a significance value of 0.624. Fenomena penumpukan sampah membutuhkan kesadaran kolektif dan keterlibatan masyarakat dalam mengatasi dan mencegah intensitas penumpukan sampah. Namun, era digital telah membuka banyak peluang bagi Pandawara Group dalam penyebaran gerakan sosial efektif. Gerakan sosial dilakukan oleh Pandawara Group melalui platform TikTok dengan tujuan mengurangi sampah dan mengharapkan kesadaran menjaga kebersihan masyarakat Indonesia tertanam sebagai upaya penanganan fenomena penumpukan sampah. Oleh karena itu peneliti memilih topik pengaruh konten TikTok Pandawara Group terhadap pengikutnya dalam menjaga kebersihan. Penelitian ini menggunakan teori new media, komunikasi persuasif, dan teori perilaku terencana sebagai indentifikasi penelitian. Penelitian ini menggunakan pendekatan kuantitatif dengan metode penelitian deskriptif. Teknik pengambilan sampel menggunakan Probability Sampling - Simple Random Sampling dengan rumus Cochran melalui pengumpulan data metode kuesioner. Total responden dalam penelitian berjumlah 96 orang. Populasi dan sampel penelitian merupakan followers TikTok Pandawara Group berusia remaja-dewasa (15-35 tahun). Penelitian menemukan nilai korelasi Spearman Rank bahwa terdapat pengaruh signifikan sebesar 0,001, terdapat kekuatan hubungan sangat kuat dan searah dengan nilai sebesar 0,783 terhadap konten TikTok dengan behaviour change. Penelitian ini menyertakan hasil Crosstabs Spearman Correlation dengan tujuan memperdalam makna penelitian melalui kategori usia dan konten TikTok dengan nilai signifikansi 0,891, kategori usia dan perubahan perilaku dengan nilai signifikansi 0,624.